Health monitoring of induction motor with impedance analysis and artificial intelligence - Lee, Kai Quan (Nanyang Technological University, 2022)
The induction motor is utilized in almost all technological applications, and it is known as one of the industry’s workhorses. In every system, it is critical to ensure that the induction motor operates safely and reliably to prevent any personnel from dangerous hazards.